2010
DOI: 10.3109/14767051003678069
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes based on the gestational age of midtrimester preterm premature rupture of membranes

Abstract: While neonatal survival improves at later GAs of mtPPROM, morbidity continues to be high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
4
16
0
Order By: Relevance
“…Also, chorioamnionitis was a significant predictor of poor fetal outcome similar to a study conducted in China. 39 The earlier gestational age at PPROM in the present study was significantly associated with poor fetal outcome which agrees with other studies. 8, 22 , 40 This is explained by the fact that incidence of respiratory distress syndrome and the length of hospital stay are related to gestational age.…”
Section: Methodssupporting
confidence: 92%
“…Also, chorioamnionitis was a significant predictor of poor fetal outcome similar to a study conducted in China. 39 The earlier gestational age at PPROM in the present study was significantly associated with poor fetal outcome which agrees with other studies. 8, 22 , 40 This is explained by the fact that incidence of respiratory distress syndrome and the length of hospital stay are related to gestational age.…”
Section: Methodssupporting
confidence: 92%
“…PROM is a well-known risk factor for intrauterine infection [4155]. Several investigators have suggested that MSAF is highly associated with infection, including endometritis and chorioamnionitis [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…A number of papers have been published describing fetal and neonatal outcomes after PROM before 24 weeks gestation . It is difficult to compare their results, however, due to variations in the characteristics of study populations, clinical management strategies used, and reported outcomes.…”
mentioning
confidence: 99%
“…Survival rates reported in the literature on pregnancies complicated by PROM before 24 weeks vary significantly. Studies published in the last decade report that 26% to 56% of these pregnancies result in the birth of a neonate who survives to discharge . The quoted proportion of babies admitted to a neonatal nursery who survive to hospital discharge varies from 62 to 79% .…”
mentioning
confidence: 99%